2016
DOI: 10.1016/j.athoracsur.2016.02.098
|View full text |Cite|
|
Sign up to set email alerts
|

The Society of Thoracic Surgeons Lung Cancer Resection Risk Model: Higher Quality Data and Superior Outcomes

Abstract: Background The Society of Thoracic Surgeons (STS) creates risk adjustment models for common cardiothoracic operations for quality improvement purposes. Our aim was to update the lung cancer resection risk model utilizing the STS General Thoracic Surgery Database (GTSD) with a larger and more contemporary cohort. Methods We queried the STS GTSD for all surgical resections of lung cancers from January 1, 2012 through December 31, 2014 Logistic regression was used to create three risk models for adverse events:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
152
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(168 citation statements)
references
References 20 publications
6
152
2
2
Order By: Relevance
“…Male and elderly patients are more likely to developing MPCs after lung resection. Fernandez et al [2016] indicated that being male and elderly patients have consistently been identified as negative predictors of major postoperative complications after lung cancer surgery (23). Perioperative mortality in male patients was also significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Male and elderly patients are more likely to developing MPCs after lung resection. Fernandez et al [2016] indicated that being male and elderly patients have consistently been identified as negative predictors of major postoperative complications after lung cancer surgery (23). Perioperative mortality in male patients was also significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…The field of cardiothoracic surgery is fortunate to have Generation of risk models for lung cancer resection from the GTSD (6,20,21) enable thoracic surgeons to quantify the risk of operative mortality and major morbidity based on patient characteristics. While surgeons can use this information for clinical decision making and preoperative patient counseling, STS risk models are limited to 30-day outcomes.…”
Section: Editorialmentioning
confidence: 99%
“…While consensus on the precise definition of "high risk" patients for pulmonary resection remains elusive (10), risk models for 30-day mortality and postoperative morbidity demonstrate the importance of patient-dependent variables as harbingers of poor outcomes (6,11,12). However, traditional risk calculators do not facilitate comparison of cancer and noncancer specific mortality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first of them is the Thoracoscore, derived from the national French database, Epithor (1). The second to be mention is the database of the Society of Thoracic Surgeons (2). The most recent attempt to create improved risk model was presented during the conference of the European Society of Thoracic Surgeons (ESTS) in Naples in 2016, and published thereafter in the European Journal of Cardiothoracic Surgery (3).…”
mentioning
confidence: 99%